Intra-articular depot forming drug delivery system for osteoarthritis - Freddi, Matthew James (2012)
Osteoarthritis (OA) is a chronic degenerative disease of the joint. Current treatments for this disease (such as glucocorticoid steroids) aim to reduce pain and increase mobility. Intra-articular injection is used in OA as treatment can be targeted to affected joints only. There is currently a lack of sustained release formulations for intra-articular injection.